Study of catheter related infections in patients admitted in ICU of a tertiary care centre - Bhatt, Ankita S.; Paritekar, Anita (International Journal of Research in Medical Sciences, 2025)
Background: Catheter-related infections (CRIs) are a significant cause of morbidity and mortality in critically ill patients, particularly in intensive care units (ICUs). This study aimed to assess the incidence, microbiological profile, associated complications, and outcomes of CRIs in patients admitted to the ICU of a tertiary care hospital. Methods: A facility-based longitudinal study was conducted in the ICU of a tertiary care center on patients >12 years old requiring indwelling catheters for >48 hours. Clinical, laboratory, and microbiological data were collected, with blood cultures analyzed using the BacT/ALERT 3D system. Statistical analysis was performed using SPSS v23.0, with p<0.05 considered significant. Results: The mean age of 3.6±9.2 years (range: 21–80 years). The incidence of CRI was 28%, with an infection rate of 24.65 per 1000 catheter-days. The most commonly isolated pathogen was Staphylococcus aureus (32.14%), followed by Klebsiella pneumoniae (25%), Enterococcus (17.86%), Escherichia coli (14.29%), and Pseudomonas aeruginosa (10.71%). K. pneumoniae was significantly associated with Foley’s catheter (p<0.05). The most common complications included sepsis (17.86%), urinary tract infections (17.86%), and acute pyelonephritis (7.14%). The mortality rate was 14.29%, with renal failure (14.29%), multiple organ dysfunction syndrome (10.71%), and septic shock (7.14%) as major contributors. However, 35.71% of patients had favorable outcomes. Conclusions: The findings underscore the need for strict aseptic techniques, routine catheter care, early catheter removal, and robust antimicrobial stewardship programs. Preventive measures, including infection control protocols and surveillance systems, can significantly reduce CRI incidence and improve patient outcomes.